Impact of short and long exposure to cafeteria diet on food intake and white adipose tissue lipolysis mediated by glucagon-like peptide 1 receptor - Mattar, Pamela; Jaque, Cristian; Teske, Jennifer A.; Morselli, Eugenia; Kerr, Bredford; Cortés, Víctor; Baudrand, Rene; Perez-Leighton, Claudio E. (Frontiers in Endocrinology, 2023)
The modern food environment facilitates excessive calorie intake, one of the major drivers of obesity. Glucagon-like peptide 1 (GLP1) is a neuroendocrine peptide that has been the basis for developing new pharmacotherapies against obesity. Activation of the GLP1 receptor (GLP1R) expressed in central and peripheral tissues reduces food intake, increases the expression of thermogenic proteins in brown adipose tissue (BAT), and enhances lipolysis in white adipose tissue (WAT). Obesity decreases the efficiency of GLP1R agonists in reducing food intake and body weight. Still, whether exposure to palatable food during the early development of obesity reduces the effects of GLP1R agonists on food intake and adipose tissue metabolism remains undetermined. Further, whether GLP1R expressed in WAT contributes to these effects is unclear. We examined whether two models of early exposure to a cafeteria (CAF) diet reduce the effects of central and peripheral administration of a GLP1R agonist, exendin-4 (EX4), on food intake, expression of thermogenic BAT proteins, and WAT lipolysis. During intermittent-short exposure to CAF diet (3 h/d for 8 days), third ventricle injection (ICV) and intra-peritoneal administration of EX4 reduced palatable food intake. Yet, during a longer-continuous exposure to CAF diet (24 h/d for 15 days), only ICV EX4 administration reduced food intake and body weight. However, this exposure to CAF diet blocked the increase in uncoupling protein 1 (UCP1) caused by ICV EX4 administration observed in mice fed control diet. Finally, GLP1R expression in WAT was minimal, and EX4 failed to increase lipolysis ex-vivo in WAT tissue samples from mice fed CAF or control diet for 12 weeks. Overall, these data show that exposure to a CAF diet during the early stages of obesity alters the effects of peripheral and central GLP1R agonists and that WAT does not express a functional GLP1R receptor. These data support that exposure to the obesogenic food environment, without the development or manifestation of obesity, can alter the response to GLP1R agonists.